Estado de la información sobre la gerencia de empresas constructoras (2014)
The project seeks to investigate and contribute to the knowledge construction of the current state of the construction industry, the knowledge of the nature and specificity of management practices and organizational reality of the construction companies. It seeks to contribute, from their results and products, to the construction of a theoretical framework as a basis for the debate and discussion about solutions for a better performance of companies in this sector.